1996
DOI: 10.1111/j.1440-6055.1996.tb01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory‐Based, Insecticide Efficacy Studies on Field‐Collected Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) and Implications for its Management in Australia

Abstract: Two field collected strains of western flower thrips, Frankliniella occidentalis, were tested against proprietary and experimental formulations of insecticide. Thrips were tested using a novel method whereby thrips were confined in testing units throughout all stages of the bioassay procedure. The bioassay technique proved to be quick and robust. Of the chemicals tested, the two non-registered compounds chlorfenopyr and fipronil were most active against field-collected F. occidentalis. The field-collected stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Confining them in an enclosed space with plant leaves can cause problems with high humidity and condensation in which they can drown. Adult thrips can be anaesthetised and sprayed together with leaf discs (Herron et al 1996), or the insects can be exposed to leaf discs coated in insecticide (Martin & Workman 1994). The former simulates field spraying where the insects may be wetted by the insecticide as well as be exposed to residues on the food plants.…”
Section: Discussionmentioning
confidence: 99%
“…Confining them in an enclosed space with plant leaves can cause problems with high humidity and condensation in which they can drown. Adult thrips can be anaesthetised and sprayed together with leaf discs (Herron et al 1996), or the insects can be exposed to leaf discs coated in insecticide (Martin & Workman 1994). The former simulates field spraying where the insects may be wetted by the insecticide as well as be exposed to residues on the food plants.…”
Section: Discussionmentioning
confidence: 99%
“…10) A. gossypii has also become resistant to fenvalerate at high and extremely high levels in several other countries. 10,12,[14][15][16][17][18][19][20][21] After having studied A. gossypii resistance to numerous insecticides in Australia, Herron et al [15][16][17] predicted that resistant A. gossypii have the potential to seriously impact the Australian cotton industry and their resistance management is now incorporated into the resistance management strategy for Australian cotton. In the past few years, neonicotinoid insecticides have been gradually used to control A. gossypii and other piercing-sucking pest insects in China.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, Kay and Herron (2010) demonstrated that fipronil, spinosad, and methamidophos had the greatest impact on adult and nymph stages. In another study to determine the most effective insecticides for the control of WFT, insecticides toxicity was tested in the LC99.99 and results showed that fipronil, with two formulations of WG and SC, came out as one of the most effective (Herron et al 1996). Kontsedalov et al (1998) evaluated the effect of abamectin, carbosulfan, methiocarb, monocrotophos, methamidophos, cypermethrin, and acrinathrin on fertility, mortality, and feeding behaviour of the adult F. occidentalis and the effect of abamectin, carbosulfan, methiocarb, and acrinathrin on immature stages in Israel.…”
Section: Biology and Problems Concerning Frankliniella Occidentalismentioning
confidence: 99%